Process Optimisation as Exemplified by School Cafeteria Work Organisation - Mariusz Chmielewski; Ewa Malinowska (Scientific Journal of Gdynia Maritime University, 2022)
The aim of this paper is to present suggestions for optimisation of the process of meal preparation in schools, which would lead to a reduction in the operating costs of the facility and more effective use of the resources in question. As a result of the research it was found that in the organisation studied there exists a real possibility of staffing reductions from 4 to 3.5 full-time jobs, which would directly translate into a reduction in the costs related to running an institutional catering establishment. The schedule prepared also enabled determining the shortest possible time of performing the entire meal preparation process, which also constitutes the critical path.